Comparative Study on Lipase Immobilized onto Organo-Cation Exchanged Kaolin and Metakaolin: Surface Properties and Catalytic Activity - Hana Meftah Elgubbi; Siti Salhah Othman; Farah Wahida Harun (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Clay mineral has received much attention to be used as biocatalysts as it is cheaper, easily available and environmentally friendly. However, the use of unmodified clay, in particular kaolin for enzyme immobilization showed unsuitability of this support due to its negative charge. In this study, the hydrophobic properties of kaolin and metakaolin (kaolin heated to 650 °C) were adjusted by the intercalation with benzyltriethylammonium chloride (BTEA-Cl), at concentrations 2.0 times the cation exchange capacities (CEC) of the clays. The supports were then used for immobilization of lipase from Candida rugosa (CRL). From the study, the highest percentage of lipase immobilization was achieved (70.14%), when organo-modified metakaolin (2.0 MK) was used. The supports as well as the immobilized biocatalysts were then characterized by X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, and nitrogen adsorption techniques. Comparisons of the efficiencies of immobilized with free CRL in the synthesis of nonyl hexanoate showed that immobilized CRL achieved enzymatic activities of between 5.24×10−3 to 3.63×10−3 mmol/min/mg, while free CRL achieved enzymatic activity of 3.27×10−3 mmol/min/mg after 5 h of reaction at 30 ℃. The immobilized CRLs also maintained 70.81% – 80.59% thermostabilities at 70 ℃ as compared to the free CRL (28.13%). CRL immobilized on 2.0 NK and 2.0 MK also maintained 38.54% and 62.56%, respectively, of the initial activities after 10 continuous cycles, showing the excellent stability and reusability of the immobilized lipases, suitable as substitute for expensive, hazardous catalysts used in industries. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).